Wideband Dual-linear Polarized Stacked Patch Antenna with Asymmery Feeding - Qingyuan Fang; Song Lizhong (Institute of Advanced Engineering and Science, 2014)
The narrow working bandwidth of microstrip antennas limits their applications in in radar and communication systems. Staked patch antenna based on aperture coupling and asymmetry feeding technique was proposed in this paper. A cross-shape aperture imbedded in the ground plane with asymmetry feeding structure provided a relative wideband electromagnetic coupling and allowed a high isolation between two orthogonal ports.The asymmetry feeding structure was composed of two microtrip lines locating above and under the ground plane. U-shape microtrip line adjusted microstrip feeding line characteristic impendence with antenna input impendence in a broad band. Experimental results indicated that an impendence bandwidth of 35.3%, better than 4.5dBi antenna gain, better than 30dB isolation and good cross-polarization were available. Measured results proved that stacked patches using asymmetry feeding structure through aperture coupling to expand working frequency and realize dual-linear polarization was effective. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3974